أثر السياسة الجبائية على قطاع الصناعة خارج المحروقات في الجزائرالفترة 1990-2020 - العقون زهرة (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
ملخص هدفت هذه الدراسة عرض أثر السياسة الجبائية على قطاع الصناعة خارج المحروقات في الجزائر خلال الفترة ،0101-0991على اعتبار القطاع الصناعي أحد الآليات القاعدية لدفع عجلة التنمية الاقتصادية بالجزائر، لذلك سعت الدولة الجزائرية لإصلاح سياستها الجبائية بهدف تشجيع وتطوير استثماراتها في قطاع الصناعة خارج المحروقات وذلك عن طريق منح تحفيزات جبائية من خلال سن قوانين ومراسيم خاصة، حيث سعت جاهدة إلى إعادة توجيه الاقتصاد الوطني نحو اقتصاد منتج خارج المحروقات. وتم تناول موضوعنا بالاعتماد على جانب نظري تم التطرق فيه إلى مجموعة من المفاهيم الأساسية حول السياسة الجبائية، وكذا أهم الإصلاحات المطبقة عليها في الجزائر منذ ،0991التي تم من خلالها استحداث ضرائب جديدة متمثلة في الضريبة على الدخل الإجمالي، والضريبة على أرباح الشركات والرسم على القيمة المضافة، وكان الهدف من هذه الإصلاحات هو سد لثغرات النظام السابق، وتبسيط النظام الضريبي وتخفيف العبء الضريبي. كما تم التطرق إلى القطاع الصناعي في الجزائر الذي يعتبر المؤشر الرئيسي للتنمية والتقدم الاقتصادي للدولة، حيث تناولنا فيه ماهية الصناعة والمراحل التي شهدها القطاع الصناعي منذ الاستقلال، وأهم التحديات التي يواجهها ومكامن الخلل فيه وأهم الحلول الممكنة، كما تم التطرق إلى تقييم أداء النظام الجبائي و أداء القطاع الصناعي، و التحفيزات المقدمة لتشجيع القطاع الصناعي، لكن فعالية النظام الجبائي الج ازئري ظلت محدودة لفشل احلال الجباية العادية محل الجباية البترولية، وبقيت حصيلة الجباية العادية تقتصر على الضرائب غير مباشرة وهذا ما تظهره كثرة التعديلات الضريبية. أما الجانب التطبيقي فقد تم قياس أثر السياسة الجبائية على قطاع الصناعة خارج المحروقات للفترة الممتدة بين ،0101-0991باستخدام منهج الانحدار الذاتي لفترات الابطاء الموزع ،ARDLفتوصلنا أن هناك قدرة تفسيرية عالية للنموذج، وأن نتائج التقدير جميع المتغيرات الخاصة بالسياسة الجبائية من ناحية الإشارة جاءت مطابقة مقارنة في كل من المدى القصير والمدى الطويل، أما معامل حد تصحيح الخطأ ذات معنوية عالية وهذا ما يؤكد دقة العلاقة التوازنية طويلة الأجل وهذا ما حققته إحصائسة فيشر المحسوبة في نتائج اختبار الحدود ،Bound Testمما يدل على قوة ارتباط المتغيرات المفسرة بالمتغير التابع، وهذا ما يؤكد صحة الفرضية الرئيسية للدراسة القياسية. الكلمات المفتاحية: سياسة جبائية– قطاع صناعي–– تحفيزات جبائية- اقتصاد ج ازئري- نموذج .AAbstract: Through this study, we aim to present the impact of fiscal policy on the industrial sector outside of hydrocarbons in Algeria during the period 1990-2020, given that the industrial sector is considered one of the basic mechanisms for driving economic development in Algeria. Therefore, the Algerian state sought to reform its fiscal policy with the aim of encouraging and developing its investments in the industrial sector outside Hydrocarbons, by granting tax incentives through the enactment of special laws and decrees, as it strived to redirect the national economy towards a productive economy outside of hydrocarbons. Our topic was addressed by relying on a theoretical aspect in which a set of basic concepts about fiscal policy were addressed, as well as the most important reforms applied to it in Algeria since 1990, through which new taxes were introduced, represented by the tax on gross income, the tax on corporate profits, and the tax on value. In addition, the aim of these reforms was to fill the loopholes of the previous system, simplify the tax system and reduce the tax burden. The industrial sector in Algeria, which is considered the main indicator of development and economic progress of the state, was also discussed. We discussed the nature of industry and the stages that the industrial sector has witnessed since independence, the most important challenges it faces, its shortcomings, and the most important possible solutions. It was also touched upon to evaluate the performance of the tax system and The performance of the industrial sector, and the incentives provided to encourage the industrial sector, but the effectiveness of the Algerian tax system remained limited due to the failure to replace petroleum taxation with regular taxation, and the proceeds of regular taxation remained limited to indirect taxes, and this is demonstrated by the large number of tax amendment. As for the applied aspect, the impact of the tax policy on the nonhydrocarbon industry sector was measured for the period extending between 1990-2020, using the autoregressive distributed lag period (ARDL) approach. We found that there is a high explanatory power for the model, and that the results of estimating all variables related to the tax policy in terms of sign were... Comparative matching in both the short run and the long run. The coefficient of the error correction term is highly significant, and this confirms the accuracy of the long-run equilibrium relationship, and this is what was achieved by the Fisher statistic calculated in the results of the Bound Test, which indicates the strength of the association of the explained variables with the dependent variable, and this This confirms the validity of the main hypothesis of the standard study. Key words: Tax policy - industrial sector - tax incentives - Algerian economy - ARDL model
Keywords: سياسة جبائية; قطاع صناعي; تحفيزات جبائية; إقتصاد جزائري; AEDL